2012
DOI: 10.5713/ajas.2012.12240
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Defaunation on Fermentation Characteristics and Methane Production by Rumen Microbes In vitro When Incubated with Starchy Feed Sources

Abstract: An in vitro experiment was conducted to examine the effects of defaunation (removal of protozoa) on ruminal fermentation characteristics, CH4 production and degradation by rumen microbes when incubated with cereal grains (corn, wheat and rye). Sodium lauryl sulfate as a defaunation reagent was added into the culture solution at a concentration of 0.000375 g/ml, and incubated anaerobically for up to 12 h at 39°C. Following defaunation, live protozoa in the culture solution were rarely observed by microscopic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 45 publications
5
17
0
2
Order By: Relevance
“…1). This finding is consistent with that of a previous study of the effects of defaunation on the fermentation characteristics of starchy feed sources, which revealed that rumen ciliates were eliminated by adding SDS after 1 h of incubation [18]. Surfactants react with cholesterol in eukaryotic cell membranes [19], which alter membrane fluidity and permeability via increased unsaturation of lipids [20,21].…”
Section: Effect Of Sds Addition On Pretreatment With Rumen Fluidsupporting
confidence: 92%
“…1). This finding is consistent with that of a previous study of the effects of defaunation on the fermentation characteristics of starchy feed sources, which revealed that rumen ciliates were eliminated by adding SDS after 1 h of incubation [18]. Surfactants react with cholesterol in eukaryotic cell membranes [19], which alter membrane fluidity and permeability via increased unsaturation of lipids [20,21].…”
Section: Effect Of Sds Addition On Pretreatment With Rumen Fluidsupporting
confidence: 92%
“…Saponin is known to inhibit the growth of acetate-producing bacteria (e.g., Butyrivibrio fibrisolvens ) and reduce the population of protozoa by reacting with cholesterol in the membrane of protozoa in the rumen [21], causing protozoa to rupture [22]. Protozoa elimination through defaunation can reduce the ratio of acetate to propionate [22,23,24]. This may be one of the reasons why a 4.5% licorice root extract supplementation reduced the ratio of acetate to propionate in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, those three inhibitors at the above concentrations were further evaluated with rumen fluid containing all the diverse protozoal and other microbial species typically found in the rumen of dairy cows. SDS, which was effective in achieving in vitro defaunation of rumen microbiota (Qin et al, 2012), was included at 1.44 mmol/L as a positive control for defaunation. A stock solution of each inhibitor was prepared aseptically in water, except for PMSF, which is insoluble in water, that was dissolved in absolute ethanol.…”
Section: Methodsmentioning
confidence: 99%